EXPERT SYSTEM FOR DETECTION OF SKIN ON THE FACE IN THE D'ANGELS BEAUTY CLINIC - Yuli Krismawati (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2021)
The role of facial beauty experts is very important to identify the type of facial skin and provide the right treatment solution for each type of facial skin. From this, an expert system is needed to help provide solutions by building an expert system that can identify the type of facial skin by including treatment solutions. The forward chaining method chooses based on considerations in the IF logic process of the If-Then, AND OR rules, and this method seeks the combination of the highest trust value. to assist aesthetic doctors in documenting medical knowledge and experience that can be used later by nurses in detecting skin types on the face. From the results of the research, it was concluded that an expert system was built to detect the type of skin on the face at the D'Aangels beauty clinic that can determine the type of skin without coming to the location of the D'Aangels beauty clinic